A relação da personalidade dos product owners no sucesso de projetos ágeis: o papel mediador da orientação à meta - Marcos, Alexandre Magno Labat (2023)
The objective of this dissertation is to investigate the relationship between Product Owner’s personality and the project success, considering team and client perspectives, mediated by the learning goal orientation, and considering the influence of the agile environment. Projects have been considered more and more important, due to their relationship with the performance of organizations, with business value and with strategic objectives. This fact can generate competitive advantage, even considering that a significant number of projects fail. One of the success factors of projects is the behavioral skills of team members and managers responsible for the project’s performance. These skills may be influenced by the professional’s personality traits. Learning Goal Orientation is a motivational state, related to some personality traits, such as conscientiousness and neuroticism, which influence behavior. The Upper Echelon Theory considers that performance and outcomes are partially predicted by the personal characteristics of the top team. However, there is a gap to be explored in the literature, which is the role of middle managers, in this case, the Product Owners and their relationship in the project success due to their managerial discretion, considering the learning motivation. The method used in this research is a quantitative study, performed with linear regression with mediation, considering project managers from Project- based Organizations, where project management has a more relevant strategic impact. We validated the short scale, through questionnaires, with reverse translation and semantic validation of 15 items (CBF-PI-15), for a sample of 323 professionals, 163 of which from projects. Then we tested and validated the questionnaire with 610 project managers, including 346 product owners. Data analysis for validation of the scale was performed with the software Factor Version 12.01.02, and through ANOVA, using Fisher's MSD (Minimum Significant Difference). For performing the analysis of structural equation modeling, we used the SmartPLS software. The study results indicate that learning goal orientation mediates the relationship between conscientiousness and neuroticism, which should contribute to studies of project behavior by assessing the mediation of the relationship between personality traits and impact on the team of agile projects and their customers.